Dirham: Problematika Mata Uang Solusi di Tengah Krisis - Diana Ambarwati (Hikmah: Journal of Islamic Studies, 2019)
The getting worse of domestic currency, the more people will speculate on the system of currency usage. It will appear parties argue that the currency usage is no longer relevant in today’s monetary sistem. The phenomenon then become a strong reason to impost bi-metal currency which are gold dinar and silver dirham. In this article, presented problematics of imposing bi-metal currency, which is dinar dirham -- that can be used as solution in the midst of economic crisis or precisely it will lead to a new polemic. Finally, it was found that the dinar and dirham can not be the absolute solution to handle currency crisis. Because, the limited availability of gold become the greatest obstacle, less simple, and can be the trigger of crime. Besides that, crisis problem is not merely currency problem, but payment balance, interrelation of foreign transaction in which the economic condition of other countries as partners. Keywords: Dinar, Dirham, Solutions, Crisis Semakin terpuruknya nilai mata uang domestik, maka akan semakin banyak yang berspekulasi tentang sistem penggunaan mata uang. Muncullah pihak-pihak yang mensinyalir, jika penggunan mata uang, sudah tidak lagi relevan dengan kondisi sistem moneter yang kekinian. Fenomena tersebut yang kemudian menjadi alasan kuat untuk kembali memberlakukan mata uang dwi logam yakni dinar emas dan dirham perak. Dalam artikel ini ditampilkan problematika pemberlakuan mata uang dwi logam, yaitu dinar dirham—dapat dijadikan solusi di tengah-tengah krisis ekonomi atau justru akan memunculkan polemik baru. Akhirnya, ditemukan jawaban bahwa dinar dan dirham tidak secara mutlak dapat menjadi solusi atas krisis yang terjadi. Sebab, ketersediaan emas yang terbatas menjadi kendala terbesar, kurang praktis, dan dapat memicu kejahatan. Selain itu, persoalan krisis bukan semata-mata persoalan mata uang tetapi keseimbangan neraca pembayaran, keterkaitan transaksi luar negeri yang kondisi ekonomi negara lain sebagai mitra. Keywords: Dinar, Dirham, Solusi, Krisis